The Effect of Service Quality on Customer Satisfaction and Loyalty in Cargo Companies in Istanbul - ZAINELDEEN, NOUR (İstanbul Kültür Üniversitesi, 2025)
This study aims to examine how service quality impacts customer satisfaction and customer loyalty in cargo service industry in Istanbul, Turkey, and the mediating role of customer satisfaction in the relationship between service quality and customer loyalty. Although previous research has examined service quality and satisfaction in the cargo sector, few have evaluated customer loyalty as a dependent variable, and none have thoroughly explored the mediating effect of customer satisfaction from the perspective of individual cargo customers in Istanbul—a major logistics hub with distinct market dynamics. Using a quantitative research design, data were collected from 303 individual cargo service users during April and May 2025 through a structured online questionnaire. The questionnaire was based on established measurement scales: SERVQUAL, Customer Satisfaction, and Customer Loyalty. The findings were analyzed using SPSS, employing descriptive, reliability and validity tests, correlation, regression, and mediation analyses. Results suggest that service quality has a significant effect on not only customer satisfaction but also customer loyalty, and that customer satisfaction acts as a partial mediator. This study makes a contribution to the service marketing literature as it fills an important gap and provides useful insights for cargo firms that seek to improve customer satisfaction and develop customer loyalty in a competitive urban market.
Keywords: Cargo; Logistics; Service Quality; Customer Satisfaction; Customer Loyalty